Phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent as well as preparation method and application thereof
By preparing the phosphorylated ZIF-8/bamboo charcoal/chitosan-tannin acid composite adsorbent, the problems of large amount of adsorbent, poor stability and low selectivity in the treatment of uranium-containing wastewater in the prior art were solved, and the uranium adsorption effect was achieved with high efficiency, stability and good selectivity, and good circulation and regeneration performance.
Patent Information
- Application Number
- CN202510002191.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art has problems in the treatment of uranium-containing wastewater with large amounts of adsorbents, poor stability, low selectivity, and post-adsorption of materials and secondary pollution.
The phosphorylated ZIF-8/bamboo charcoal/chitosan-tanninic acid composite adsorbent was used to combine ZIF-8 with bamboo charcoal by preparation method, and cure and phosphorylation by chitosan-tanninic acid cross-linking to form an efficient adsorbent.
It has achieved efficient adsorption of uranium, with high adsorption selectivity and adsorption capacity, and has small amounts and high stability. It can efficiently extract uranium from low-concentration uranium-containing wastewater and has good circulation and regeneration performance.
Smart Images

Figure CN119565580A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of uranium-containing wastewater treatment, and in particular to a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent and a preparation method and application thereof. Background Art
[0002] With the development of nuclear energy industry, the treatment of uranium-containing wastewater has become an increasingly serious environmental problem. As a radioactive element, the accumulation of uranium in the environment poses a serious threat to human health and ecosystems.
[0003] At present, the treatment methods for uranium-containing wastewater mainly include biological extraction, adsorption, complex precipitation, membrane separation and chemical reduction, but these methods all have certain limitations. Although the adsorption method can effectively reduce the migration of U(VI), the disposal of the adsorbed material and the problem of secondary pollution are still challenges. Traditional adsorbents often have limited adsorption capacity and are easily interfered by other ions in practical applications, resulting in low selectivity. The chemical reduction method reduces U(VI) to U(IV) to reduce its solubility and mobility, but U(IV) is easily oxidized in the air and re-forms easily soluble and mobile U(VI), limiting its long-term stability. Although membrane separation technology has the advantages of high efficiency and easy operation, it has problems such as high cost, membrane pollution and limited processing capacity, which limit its application in large-scale uranium-containing wastewater treatment. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent, wherein the prepared adsorbent has high adsorption selectivity and adsorption capacity for uranium, and has low dosage and high stability.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent, comprising the following steps:
[0006] 1. Preparation of ZIF-8 / bamboo charcoal (ZB):
[0007] Take bamboo charcoal (BC), Zn (NO 3 ) 2 6H 2 O solution and 2-methylimidazole solution are stirred in a container, and then centrifuged to obtain a precipitate, which is ZIF-8 / bamboo charcoal;
[0008] 2. Preparation of chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material (ZBCT):
[0009] Add tannic acid to a container filled with water and stir, then add chitosan, ZIF-8 / bamboo charcoal and glacial acetic acid to the container and continue stirring, then add glutaraldehyde solution to the container, shake and react until the sol ages, and freeze-dry to obtain a chitosan-tannic acid cross-linked and cured ZIF-8 / bamboo charcoal composite material;
[0010] 3. Preparation of phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent (P-ZBCT):
[0011] Chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material and methanesulfonic acid were mixed in a container, and then P 2 O 5 The mixture was stirred, placed in ice water, washed and dried to obtain a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent.
[0012] Furthermore, in step 1, every 0.2 g of bamboo charcoal corresponds to 100 mL of Zn(NO 3 ) 2 6H 2 O solution and 100 mL of 2-methylimidazole solution. For example, bamboo charcoal is 0.2 g, Zn(NO 3 ) 2 6H 2 O solution is 100mL, and 2-methylimidazole solution is 100mL.
[0013] Furthermore, in step 1, the Zn(NO 3 ) 2 6H 2 The concentration of the O solution is 100 mmol / L, and the concentration of the 2-methylimidazole solution is 400 mmol / L.
[0014] In step 1, after the precipitate is obtained by centrifugation, it is washed and dried. The specific steps of washing include: washing with ethanol and deionized water for multiple times (for example, 3 times). The drying temperature is 80° C. and the drying time is 12 hours.
[0015] Furthermore, in step 2, the mass ratio of tannic acid, chitosan, and ZIF-8 / bamboo charcoal is 1:2:1. For example, tannic acid is 0.3 g, chitosan is 0.6 g, and ZIF-8 / bamboo charcoal is 0.3 g.
[0016] Further, in step 2, every 0.3g of ZIF-8 / bamboo charcoal corresponds to 0.3g of tannic acid, 0.6g of chitosan, 0.6mL of glacial acetic acid and 1mL of glutaraldehyde solution. For example, ZIF-8 / bamboo charcoal is 0.3g, tannic acid is 0.3g, chitosan is 0.6g, glacial acetic acid is 0.6mL, and glutaraldehyde solution is 1mL. The concentration of the glutaraldehyde solution is 0.1%.
[0017] Among them, in step 2, the stirring time before and after is 2h and 2h respectively.
[0018] Among them, in step 2, the specific steps of the shaking reaction include: shaking in a constant temperature shaking box (150r / min, 45°C) for 24h.
[0019] Wherein, in step 2, the freeze-drying time is 48 hours.
[0020] Furthermore, in step 3, 1.0 g of chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material corresponds to 14 mL of methanesulfonic acid and 2 g of P 2 O 5 For example, the chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material (ZBCT) is 1.0 g, the methanesulfonic acid is 14 mL, and P 2 O 5 is 2g.
[0021] Wherein, in step 3, the stirring time is 1 hour and the time of placing in ice water is 3 hours.
[0022] Wherein, in step three, the specific steps of washing include: washing with ether, acetone and methanol for multiple times (for example, three times).
[0023] Among them, in step three, the specific steps of drying include: placing in a 25°C oven for drying or natural drying.
[0024] Wherein, the water involved in the above preparation method may be deionized water, and the container involved in the above preparation method may be a beaker.
[0025] Another object of the present invention is to provide a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent, which is prepared by the above-mentioned preparation method.
[0026] In addition, the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent can be used in the treatment of uranium-containing wastewater. Specifically, the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent is added to the wastewater to adsorb uranium in the wastewater.
[0027] Further, every 5 to 10 mg of phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent corresponds to 90 mL of wastewater. Preferably, every 5 mg or 10 mg of phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent corresponds to 90 mL of wastewater. For example, the wastewater is 90 mL, and the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent is 5 mg or 10 mg.
[0028] Wherein, the initial uranium concentration in the wastewater does not exceed 10 mg / L. For example, the initial uranium concentration in the wastewater is 10 mg / L or 730 μg / L.
[0029] Furthermore, the pH of the wastewater is 5-8 (such as pH=5.0, 6.0, 7.0, 8.0, preferably pH=6.0), the temperature is 288-308K (such as 288K, 298K, 308K, preferably 308K), and the adsorption time of the adsorbent is not less than 0.5h (such as 0.5-12h).
[0030] The present invention synthesizes a novel phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent (P-ZBCT), which can be used for low-dose and high-efficiency adsorption of uranyl ions in wastewater. Test results show that the low-dose adsorbent has excellent adsorption effect on uranium. The theoretical maximum adsorption amount of P-ZBCT for U(VI) is 2357.69 mg / g (308K, pH=6.0). Its adsorption of uranium is a spontaneous endothermic reaction and belongs to chemical adsorption. Mechanism analysis shows that P─O, amino group and C═N on the surface of P-ZBCT play a key role in the adsorption of uranium. Competitive adsorption experiments show that the distribution coefficient of U is significantly higher than the distribution coefficient of coexisting ions. The real uranium tailings pond wastewater is adsorbed and treated, and the uranium content of the wastewater is reduced to 34 μg / L. In addition, P-ZBCT exhibits excellent cyclic regeneration performance. After 10 adsorption-desorption cycles, the adsorption rate is still 85%. Therefore, P-ZBCT has great potential in the efficient extraction of uranium from low-concentration uranium-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Middle: (a) is the scanning electron microscope (SEM) image of ZB; (b) and (c) are the SEM spectra of P-ZBCT (b: before adsorption; c: after adsorption); (d)–(i) are the element distribution diagrams of C, N, O, P, Zn and U.
[0032] Figure 2 Middle: (a) is the thermogravimetric (TG) curves of BC, ZB, ZBCT, P-CBCT and P-CBCT-U; (b) is the infrared spectra of BC, ZB, ZBCT, P-CBCT and P-CBCT-U.
[0033] Figure 3 X-ray photoelectron spectroscopy (XPS) diagram of P-ZBZT and P-ZBZT-U.
[0034] Figure 4 Schematic diagram of the effect of initial solution pH on uranium adsorption by P-ZBCT.
[0035] Figure 5Middle: (a) is a schematic diagram of the effect of contact time on the adsorption of uranium by P-ZBCT; (b) is the uranium adsorption isotherm of P-ZBCT at 288K; (c) is the uranium adsorption isotherm of P-ZBCT at 298K; (d) is the uranium adsorption isotherm of P-ZBCT at 308K.
[0036] Figure 6 Middle: (a) is the distribution coefficient (K) of different ions after P-ZBCT adsorption d ) schematic diagram; (b) schematic diagram of the cyclic adsorption and desorption results of P-ZBCT; (c) infrared spectrum of P-ZBCT after desorption; (d) XPS total spectrum of P-ZBCT after desorption. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.
[0038] This embodiment provides a novel phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent (P-ZBCT) for low-dose and high-efficiency adsorption of uranyl ions in wastewater, as follows.
[0039] 1. Preparation of composite adsorbent (P-ZBCT)
[0040] 1. Chemical reagents
[0041] 2-Methylimidazole (PubChem CID: 12749) and chitosan (CS) were purchased from Macklin Reagent Company, and analytically pure zinc nitrate hexahydrate, phosphorus pentoxide, methanesulfonic acid, glutaraldehyde, glacial acetic acid, and tannic acid were purchased from domestic companies. All reagents were AR grade.
[0042] 2. Preparation of Materials
[0043] 2.1 Preparation of ZIF-8 / bamboo charcoal: 0.2 g bamboo charcoal (BC), 100 mL Zn(NO 3 ) 2 6H 2 O solution and 100 mL of 400 mmol / L 2-methylimidazole solution were placed in a beaker and stirred at room temperature for 5 h. The precipitate was obtained by centrifugation, washed three times with ethanol and deionized water, and dried at 80 °C for 12 h to obtain ZIF-8 / bamboo charcoal (ZB).
[0044] 2.2 Chitosan-tannic acid cross-linked solidified ZB: 60 mL of deionized water was added to a beaker containing 0.3 g of tannic acid, and stirred for 2 h to completely dissolve it. Then 0.6 g of chitosan and 0.3 g of ZB were weighed, and 0.6 mL of glacial acetic acid was added, and stirring continued for 2 h. After the chitosan was completely dissolved, 1 mL of 0.1% glutaraldehyde solution was added, and the solution was shaken in a constant temperature shaker (150 r / min, 45 ° C) for 24 h until the sol was aged, and freeze-dried for 48 h to obtain chitosan-tannic acid cross-linked solidified ZB (ZBCT).
[0045] 2.3 Phosphorylation of ZBCT: Place 1.0 g of ZBCT in a beaker and add 14 mL of methanesulfonic acid to ensure uniform mixing. Place the beaker in a fume hood and add 2 g of phosphorylation. 2 O 5 , stirred for 1 hour, and then placed in ice water for 3 hours. Then washed with ether, acetone and methanol three times, placed in a 25°C oven to dry or dried naturally to obtain P-ZBCT.
[0046] 3. Adsorption Experiment
[0047] The adsorption experiment was carried out on a uranium solution prepared by diluting uranyl carbonate with ultrapure water. The adsorbent was placed in the uranium solution to determine its adsorption performance for uranium. During the experiment, it was necessary to shake moderately at 175 rpm on a shaker. The pH of the uranium solution was adjusted with nitric acid and sodium carbonate. 5 mg of the adsorbent was taken for adsorption experiments in 90 mL of uranium solution with an initial uranium concentration of 10 mg / L. The effects of pH (4–9), contact time (0.5–12 h), and temperature (15–35 °C) on the adsorption capacity of the adsorbent for uranyl ions were investigated. Adsorption efficiency (R, %), equilibrium adsorption capacity (q e , mg / g) and distribution coefficient (K d ) is calculated by the following formula.
[0048] R=(C 0 -C e ) / C 0 ×100%#(1)
[0049]
[0050] Among them C 0 (mg / L) and C e (mg / L) represent the concentrations at initial adsorption and equilibrium adsorption, respectively. V(L) represents the volume of the mixture, and m(g) represents the mass of the adsorbent.
[0051] 4. Characterization
[0052] Fourier transform infrared (FTIR) spectra of the materials were recorded from KBr pellets in the scan range of 4000–400 cm -1. Using BET (adsorbate is N 2 ) were used to analyze the specific surface area and pore size of the materials. The surface morphology of the synthesized materials was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Thermogravimetric analysis (TGA) of the materials was carried out in the range of 35-800°C. The uranium concentration was measured by UV-visible spectrophotometer (wavelength of 578nm). The low-concentration uranium content and the content of each element in the competitive adsorption experiment were determined by inductively coupled plasma mass spectrometry. X-ray photoelectron spectrometer (XPS) analyzed and recorded regional scans such as U4f, O1s, N1s and C1s.
[0053] 2. Related tests of composite adsorbent (P-ZBCT)
[0054] 1. Adsorption mechanism
[0055] ZIF-8 / bamboo charcoal was successfully prepared by in-situ growth of ZIF-8 on bamboo charcoal. Figure 1 a), showing a clear dodecahedral structure. P-ZBCT was prepared by cross-linking and curing ZIF-8 / bamboo charcoal with chitosan tannic acid and then phosphorylating it. The SEM image is shown in Figure 1 As shown in b, the surface is smooth with irregular cracks. After adsorbing uranium ( Figure 1 c), white floccules appeared on the surface of the adsorbent, and the cracks became smaller. After scanning the SEM area, the mapping image of the material surface was obtained. Figure 1 d~ Figure 1 It can be seen that the uranyl ions are evenly distributed in the two-dimensional space of the scanning area, and this distribution is related to the elements such as C, N, O, and P in the adsorbent. This confirms the successful adsorption of U(VI) by P-ZBCT. The results of the pressure pump analysis show that the specific surface area of P-ZBCT is 2.228m 2 / g, pore volume 0.052cm 3 / g, the average pore diameter is 12.435nm, and it is a mesoporous structure.
[0056] The thermal stability of P-ZBCT was evaluated by thermogravimetric analysis. Figure 2 As shown in a, the test results show that the first stage of weight loss of P-ZBCT occurs at about 100°C, which corresponds to the evaporation or removal of volatile components in the sample during the heating process, such as water or other small molecules that are easily evaporated at low temperatures. The weight loss is about 3.23%, which is less, indicating that the sample has good hydrophilicity. The second stage of weight loss occurs at about 250°C, and its weight loss is about 52.54%. The reason for the large mass loss is that the oxygen-containing functional groups in the P-ZBCT structure undergo thermal cracking within this temperature range. When heated to 800°C, 44.23% of the sample remains, indicating that P-ZBCT has good thermal stability.
[0057] The infrared spectra of bamboo charcoal (BC), ZIF-8 / bamboo charcoal (ZB), ZBZT, P-ZBZT and P-ZBZT-U are shown in Figure 2. Figure 2 b. The peaks in the figure mainly appear at 1623, 1525, 1379, 1150, 1035 and 778 cm -1 2931cm -1 The absorption peaks at 1623 cm-1 and 1663 cm-2 belong to the stretching vibration peaks of the C─H bond in the methyl ring and the imidazole ring, respectively. Compared with the infrared spectrum of ZBZT, the absorption peaks at 1623 cm-1 of P-ZBZT are -1 and 892cm -1 The new P-OH characteristic peaks at 1525 and 1150 cm -1 The characteristic absorption peak at 1422 cm is attributed to the stretching vibration of C═N and C─N. -1 The peak observed at 897 cm-1 was assigned to the stretching vibration peak of C═N─H in imidazole. -1 A new O═U═O peak appears at , confirming that the P-ZBZT material successfully adsorbs uranium.
[0058] Figure 3 ( Figure 3 a~ Figure 3 f) is the XPS spectrum image of P-ZBCT before and after uranium adsorption. From the total spectrum of P-ZBCT and P-ZBCT-U ( Figure 3 e) From the above, a U element binding energy peak appears in P-ZBCT-U. Figure 3 f, the double peaks at 392.90eV and 382.06eV are U 4f 5 / 2 and U 4f 7 / 2 The appearance of the typical characteristic peak of U(VI) further confirms the successful adsorption of U(VI). Figure 3 b) The peaks at 401.52 eV and 399.4 eV correspond to -NH 3 + and C=N, after uranium adsorption, -NH 3 + The peak shifts as the intensity decreases, indicating that the amino group participates in the reaction. In the O1s spectrum, the binding energy of P-ZBCT shows characteristic peaks of P─O and C─OH at 531.15 eV and 532.64 eV, respectively. After adsorbing uranyl ions, the P─O peak moves toward the direction of higher binding energy, indicating its binding with U(VI). Figure 3dThe peak near 133.59eV represents P2p, indicating that the material is successfully phosphorylated. The peak area representing P2p increases after adsorption, indicating that the phosphorus-containing groups participate in the adsorption of uranium. In addition, the binding energies of the C1s peak are 284.80, 286.29 and 287.76eV. The peak at 284.8eV is due to the C═C or C─C bonds that may exist in the form of sp2 or sp3 hybridization in the P-ZBCT structure. The peak near 286.29eV represents the C─O structure, revealing the existence of carbon atoms, nitrogen atoms and oxygen atoms in P-ZBCT. The peak at 287.76eV represents the C═N structure, which is mainly derived from the imidazole ring of ZIF-8. The binding energy increases by 0.16eV after adsorption, indicating that the nitrogen atom and the uranyl ion undergo a complex reaction. The above spectral analysis shows that the adsorption of uranium by P-ZBCT is related to O1s, N1s, C1s and P2p. Therefore, combined with the IR and the above XPS analysis results, it is mainly the P─O, amino group and C═N on the surface of P-ZBCT that are involved in the uranium adsorption process.
[0059] 2. Effect of pH
[0060] The pH of the solution is an important parameter because it affects the surface charge of the adsorbent and the uranium(VI). Figure 4 It can be seen that the adsorption rate of P-ZBCT gradually increases as the pH value increases from 4 to 6. At pH = 4, the surface charge of P-ZBCT is positive due to the high protonation of the amino and imidazole groups, and at this time, U(VI) is mainly in the form of UO 2 2+ Therefore, there is a strong electrostatic repulsion between them, resulting in low adsorption capacity. When pH is 4-5, U(VI) mainly exists in the form of UO 2 OH + 、(UO2) 2 (OH) 2+ ,(UO 2 ) 3 (OH) 5 + With the increase of pH value, the degree of deprotonation of P-ZBCT increases, the electrostatic repulsion gradually decreases, and the adsorption rate of uranium gradually increases. When pH ≥ 6, (UO 2 ) 2 CO 3 (OH) 3 - , UO 2 (CO 3 ) 2 2- and UO 2 (CO 3 ) 3 4-It is dominant. According to the Zeta potential, the adsorbent is positively charged at this time. Due to electrostatic attraction, as the adsorbent is deprotonated, the electrostatic attraction decreases and the adsorption rate decreases. Therefore, the maximum adsorption value is reached at pH = 6. When the pH is higher than the isoelectric point, the adsorbent is negatively charged, the electrostatic attraction is converted into electrostatic repulsion, and the adsorption rate decreases. P-ZBCT maintains a high adsorption rate for uranium in the pH range of 5.0–8.0. At pH = 8, the adsorbent still has an adsorption rate of 90% for uranium. In summary, pH has a great influence on the adsorption performance of P-ZBCT. At pH = 6.0, the adsorbent has the best adsorption effect. Therefore, further experiments will be carried out under pH = 6.0.
[0061] 3. Adsorption kinetics
[0062] Figure 5 a shows the effect of adsorption time on the uranium adsorption level. The adsorption rates of P-ZBCT reached 88.44% and 92.53% at 30min and 60min, respectively. The adsorption equilibrium was reached after 180min, and the adsorption amount reached 165.08mg / g. At the beginning of adsorption, there were a large number of free uranyl ions in the solution. At this time, P-ZBCT had abundant adsorption sites. The particle movement enabled the adsorbent to quickly capture a large number of uranyl ions. As the contact time increased, the uranyl ions and adsorption sites decreased, the adsorption rate gradually decreased, and finally reached a dynamic equilibrium.
[0063] The adsorption kinetics were studied using pseudo-first-order and pseudo-second-order equations, such as Figure 5 a, and the correlation coefficients of the results are shown in Table 1. The results show that the pseudo-second-order fitting correlation coefficient is 0.999, indicating that the adsorption of our material is mainly chemical adsorption.
[0064] Table 1 Kinetic parameters of uranium adsorption by P-ZBCT
[0065]
[0066] 4. Adsorption isotherms and adsorption thermodynamics
[0067] In order to evaluate the maximum adsorption capacity of the adsorbent, the adsorption isotherm was tested. Figure 5 c~ Figure 5 It can be clearly seen that the adsorption capacity of the adsorbent increases with the increase of uranyl ion concentration. The Langmuir and Freundlich models were used to fit the isothermal adsorption of P-ZBCT adsorbed uranium solution, and the corresponding isotherm constants were determined (Table 2). The adsorption capacity of P-ZBCT increases with the increase of temperature. It was observed that the R 2It is significantly higher than the Freundlich model. This shows that the Langmuir isotherm model fits the adsorption curve of P-ZBCT for U well. Therefore, when P-ZBCT adsorbs U, the monolayer adsorption characteristics dominate. In summary, under the conditions of 308K and pH 6, the theoretical maximum adsorption capacity of P-ZBCT for U is 2357.69 mg / g, which shows that P-ZBCT has excellent adsorption capacity for uranium.
[0068] Table 2 Isotherm parameters of uranium adsorption by P-ZBCT
[0069]
[0070] Among them, 288K, 298K, and 308K correspond to 15℃, 25℃, and 35℃ respectively.
[0071] The thermodynamic parameters determined in this example are shown in Table 3. 0 >0 indicates that the adsorption of U by P-ZBCT is an endothermic reaction. ΔS 0 >0 indicates that the randomness and disorder of the solid-liquid interface increase during the adsorption process. ΔG 0 <0 and gradually decreases with increasing temperature, which may be due to the fact that the mobility of uranium increases with increasing temperature, indicating that P-ZBCT has a higher adsorption capacity at higher temperatures. In summary, the adsorption of U(VI) by P-ZBCT is a spontaneous endothermic process, which is consistent with Figure 6 b~ Figure 6 d The results of the adsorption isotherm are consistent.
[0072] Table 3 Thermodynamic parameters of uranium adsorption by P-ZBCT
[0073]
[0074] 5. Simulated and real wastewater experiments
[0075] To investigate whether P-ZBCT has selectivity for the adsorption of uranium, mixed solutions containing U and calcium, magnesium, sodium, copper, iron, zinc, and vanadium were prepared. Figure 6 a is the distribution coefficient of different ions after adsorption (K d ), the experiment showed that P-ZBCT has a great influence on Ca 2+ Mg 2+ ,Na + ,Fe 3+ Basically no adsorption, Cu 2+ ,Zn 2+ ,V 5+ The adsorption is less, and the distribution coefficient of P-ZBCT for uranium adsorption is 17 times that of vanadium. The above results show that P-ZBCT has a high selectivity for uranium in mixed solutions containing multiple metal ions.
[0076] In order to explore the adsorption capacity of P-ZBCT on uranium in actual wastewater, uranium adsorption was carried out on low-concentration uranium tailings pond wastewater. The wastewater was taken from a uranium mine seepage water, and its uranium concentration was 730μg / L. 10mg of P-ZBCT was used to adsorb 90mL of wastewater at 298K. After 12h of adsorption, the uranium content of the wastewater was reduced to 34μg / L. The removal rate of uranium by P-ZBCT reached 95.28%, which met the limit value requirements of uranium concentration in wastewater discharge in the "Regulations on Radiation Protection and Environmental Protection of Uranium Mining and Metallurgy" (≤50μg / L), indicating that P-ZBCT has good application prospects in the treatment of low-concentration uranium-containing wastewater.
[0077] 6. Recycling
[0078] The recovery performance of P-ZBCT was verified by adsorption and desorption experiments. At 318K, HCl with a pH of 1.5 was used as the desorption solution to elute P-ZBCT after adsorbing 10 mg / L uranium. The results are shown in Figure 2. Figure 6 b. The initial uranium desorption rate was 82%. After 7 cycles of adsorption and desorption, P-ZBCT was still able to maintain a stable adsorption capacity, with an adsorption rate of 90% and a desorption rate of 92%. As the number of cycles increased, in the tenth round of adsorption and desorption, the adsorption rate of P-ZBCT on uranium was still 85%, and its desorption rate dropped to 80%. The desorbed P-ZBCT was characterized by infrared spectroscopy ( Figure 6 c), all characteristic peaks of P-ZBCT still exist, indicating that the components of P-ZBCT are not destroyed. From the XPS total spectrum ( Figure 6 d) It can be seen that no obvious peak representing uranium is detected in the desorbed material. The results show that P-ZBCT has excellent stability and is easy to recycle and reuse in practical applications.
[0079] In summary, this embodiment prepares a new composite adsorbent (P-ZBCT), which has high adsorption selectivity and adsorption capacity for uranium, and has low dosage and high stability. Dynamic and isotherm experiments show that the adsorption of uranium by P-ZBCT is mainly spontaneous chemical adsorption and endothermic reaction. In addition, the adsorption of U by P-ZBCT is more consistent with the Langmuir isotherm model. Under the conditions of 308K and pH=6, the theoretical maximum adsorption capacity of Langmuir for U reaches 2357.69 mg / g. P-ZBCT can be reused, because after 10 adsorption-desorption cycles, the adsorption rate is still 85%. Mechanism studies show that P─O, amino and C═N on the surface of P-ZBCT play a key role in the adsorption of uranium. Competitive adsorption experiments showed that the distribution coefficient of P-ZBCT for uranium was significantly higher than that of other metal ions. In the treatment of low-concentration uranium tailings wastewater, the uranium concentration was reduced to 34 μg / L, indicating that P-ZBCT has broad application prospects in the treatment of low-concentration uranium-containing wastewater.
[0080] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.
[0081] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.
Claims
1. A method for preparing a phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent, characterized in that: The steps include:
1. Preparation of ZIF-8 / bamboo charcoal: Bamboo charcoal, Zn(NO3)2·6H2O solution and 2-methylimidazole solution are stirred in a container, and then centrifuged to obtain a precipitate, namely ZIF-8 / bamboo charcoal; 2. Preparation of chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material: Add tannic acid to a container filled with water and stir, then add chitosan, ZIF-8 / bamboo charcoal and glacial acetic acid to the container and continue stirring, then add glutaraldehyde solution to the container, shake and react until the sol ages, and freeze-dry to obtain a chitosan-tannic acid cross-linked and cured ZIF-8 / bamboo charcoal composite material; 3. Preparation of phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent: Chitosan-tannic acid cross-linked ZIF-8 / bamboo charcoal composite material and methanesulfonic acid were mixed in a container, P2O5 was added and stirred, and then placed in ice water, washed and dried to obtain phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent.
2. The method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 1, characterized in that: In step 1, every 0.2 g of bamboo charcoal corresponds to 100 mL of Zn(NO3)2·6H2O solution and 100 mL of 2-methylimidazole solution.
3. The method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 1, characterized in that: In step 1, the concentration of the Zn(NO3)2·6H2O solution is 100 mmol / L, and the concentration of the 2-methylimidazole solution is 400 mmol / L.
4. The method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 1, characterized in that: In step 2, the mass ratio of tannic acid, chitosan, and ZIF-8 / bamboo charcoal is 1:2:
1.
5. The method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 1, characterized in that: In step 2, every 0.3 g ZIF-8 / bamboo charcoal corresponds to 0.3 g tannic acid, 0.6 g chitosan, 0.6 mL glacial acetic acid, and 1 mL glutaraldehyde solution.
6. The method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 1, characterized in that: In step 3, every 1.0 g of chitosan-tannic acid cross-linked and cured ZIF-8 / bamboo charcoal composite material corresponds to 14 mL of methanesulfonic acid and 2 g of P2O5.
7. Phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent, characterized in that: The composite adsorbent is prepared by the method for preparing the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent described in any one of claims 1 to 6.
8. Use of the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 7 in the treatment of uranium-containing wastewater, characterized in that: The phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent is added into wastewater to adsorb uranium in the wastewater.
9. The use of the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 8, characterized in that: Each 5-10 mg of phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent corresponds to 90 mL of wastewater.
10. The use of the phosphorylated ZIF-8 / bamboo charcoal / chitosan-tannic acid composite adsorbent according to claim 8, characterized in that: The pH of the wastewater is 5-8, the temperature is 288-308 K, and the adsorption time of the adsorbent is not less than 0.5 h.
Citation Information
Cited By
Ternary organic-inorganic hybrid material for adsorbing antibiotics in water and preparation method of ternary organic-inorganic hybrid material
CN121288779A
Chitosan-citric acid cross-linked bamboo charcoal-based composite adsorbent as well as preparation method and application thereof
CN121550967A